Ревизия классики украинской зарубежной лингвистики: гендерная проблематика в системе взглядов Юрия Шевелева (на материале статьи Über die Besonderheiten der Sprache der Frauen) - Kosmeda, Tetyana (Studia Rossica Posnaniensia, 2022)
It is typical of the modern linguistic study to reconsider the classical heritage, which makes it possible to observe the dynamics of linguistic processes and the movement vector of scientific thought, as well as to track the problems that still need to be solved nowadays. Such problems include linguistic genderology issues, in particular the description of female speech. In this regard, the little-known German-language research of Yuri Sherekh (Shevelev) Über die Besonderheiten der Sprache der Frauen (1952), which outlines the specificity of female speech at almost all language levels, appears to be of great value. This piece of research remains relevant since it makes it possible to compare the female speech features from different historical periods as well as to rethink the data on the manifestation of conservatism, archaism, negative attitude towards assimilation processes, etc. in female speech, to see the dynamics of the female linguistic worldview and the development of femininity. It seems reasonable enough to state that Shevelev laid the foundation for: 1) a comparative study of gender issues based on the Slavic languages; 2) historical and dialectal gender linguistics of the Ukrainian language; 3) national Ukrainian linguistic genderology, manifested at the level of national linguistic consciousness; 4) the study of gender opposing linguistic worldviews; 5) considering the level manifestation of gender characteristics in linguistic systems.